Een hoog IQ stelt late vermindering van cognitieve vaardigheden uit - Diesfeldt, Han F. A. (Tijdschrift voor Gerontologie en Geriatrie, 2017)
bespreking: Thorvaldsson V, Skoog I, Johansson B. IQ as moderator of terminal decline in perceptual and motor speed, spatial, and verbal ability: Testing the cognitive reserve hypothesis in a population- based sample followed from age 70 until death. Psychology and Aging. 2017;32:148–157